Analisis Strategi Pemasaran untuk Meningkatkan Volume Penjualan dan Daya Saing - Willy Tambunan; Yudi Sukmono; Luvita Okti Anggreani (Universitas Teuku Umar, 2021)
UKM Roti H-34 is one of the Small and Medium Enterprises (UKM) in Samarinda City which is engaged in the culinary field that produces unyil bread. The superior product has decreased in sales. Based on this, this study aims to determine the best alternative marketing strategy solutions to increase sales volume and competitiveness based on internal and external factors that affect the company. Marketing strategy analysis is carried out in several stages, the first is using the IFE and EFE matrices. The results obtained on the IFE matrix is 3.779, while the EFE matrix is 2.905. The second stage is the matching stage using the BCG matrix, benchmarking, IE matrix and SWOT matrix. In the BCG matrix, the results show that the market growth rate of -37% of the market share of each competing company is 0.22, 0.23, and 0.25, which indicates that the company is in the dog quadrant. In the IE matrix, it is found that UKM Roti H-34 is in cell IV, a strategy that can be used, namely growth and build. Then formulated a strategy using the SWOT matrix and obtained nine alternative strategies. The final stage is the decision stage to use QSPM for the selection of strategies that can be implemented by UKM Roti H-34. The alternative strategy that is most appropriate to be applied is to use the internet media to carry out online promotions in order to increase sales and the number of consumers with a TAS of 5.447.